Káposztafélék xantomonászos feketeerűség betegségét okozó kórokozó elleni védekezési lehetőségek értékelése szabadföldön - Czina, Miklós István; Fodor, Attila; Végh, Anita (GEORGIKON FOR AGRICULTURE, 2023)
Xanthomonas campestris pv. campestris is one of the most important pathogens of brassicas. The bacterium causes typical ’V’ shaped spots on the leaf, which are initially watery and yellowish colored, then in time became necrotic. Prevention is the most effective way to control this pathogen, so the choice of tolerant varieties is essential for successful cultivation. In our study, we evaluated the susceptibility of 9 cultivars and the effect of different natural substances (lemon juice, cinnamon, orange oil). The evaluation was based on the number of leaf symptoms. Only the infected control differed significantly from the treatments with lemon juice and cinnamon at 0,025 % concentration. The Bejo ’3415’ variety was significantly different from the other tested varieties except. However, it is justified to repeat the experiment for several years to get an accurate result of the susceptibility of the varieties to the pathogen.